2017
DOI: 10.1038/srep44937
|View full text |Cite|
|
Sign up to set email alerts
|

The Association between Diffuse Myocardial Fibrosis on Cardiac Magnetic Resonance T1 Mapping and Myocardial Dysfunction in Diabetic Rabbits

Abstract: The objective of this study was to assess the relationship between imaging surrogates for diffuse fibrosis and myocardial dysfunction. Thirty-six New Zealand white rabbits were classified into two groups: a control group (n = 18) and an alloxan-induced diabetes mellitus (DM) group (n = 18). For all rabbits, conventional ultrasonography, two-dimensional speckle tracking, and cardiac magnetic resonance (CMR) T1 mapping were performed; all of the rabbits were then sacrificed for Masson’s staining. The extracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
(36 reference statements)
4
8
0
Order By: Relevance
“…FS and EF progressively decreased in the T1DM group from 4 to 24 weeks, whereas EF was preserved; FS and EF values signi cantly differed at 16 weeks, whereas the E/A ratio signi cantly differed at 12 weeks between the T1DM and control groups. Diastolic dysfunction occurred earlier than systolic dysfunction, and the diastolic function gradually deteriorated in the T1DM group; this nding is consistent with that of previous studies [14,23] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…FS and EF progressively decreased in the T1DM group from 4 to 24 weeks, whereas EF was preserved; FS and EF values signi cantly differed at 16 weeks, whereas the E/A ratio signi cantly differed at 12 weeks between the T1DM and control groups. Diastolic dysfunction occurred earlier than systolic dysfunction, and the diastolic function gradually deteriorated in the T1DM group; this nding is consistent with that of previous studies [14,23] .…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that the ECV value was strongly correlated with CVF, and the postcontrast T1 value was moderately associated with the CVF value. The main reason is likely that the gadolinium agent (as an extracellular contrast agent) could not pass through the cell membrane and enter the cell; therefore, the postcontrast T1 value was mainly associated with the contrast agent concentration in the extracellular matrix, which is consistent with the ndings of our previous studies [23,29] and another study [28] . In addition, our study showed that the ECV value was higher than CVF, possibly because the CVF value re ects only the extracellular collagen ber content, whereas the ECV value can also indicate mucus matrix, lipid, and necrosis components outside cells.…”
Section: Discussionsupporting
confidence: 90%
“…Understanding the pathogenesis of interstitial fibrosis in the stressed heart and dissecting the mechanisms responsible for adverse cardiac outcomes are crucial to design new strategies for prevention of cardiac failure and myopathy. In an animal model, the change of ECV occurred earlier than myocardial dysfunction in diabetic rabbits (28). It is generally accepted that in the process of the pathological remodeling of cardiomyopathy, progressive accumulation of extracellular matrix components increases cardiac stiffness (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…13 Myocardial extracellular volume (ECV), which is acquired noninvasively with T 1 mapping before and after gadolinium administration, can be robustly quantified by comparing changes in relaxation rate between the pre-and postcontrast state in myocardium to blood. [14][15][16] ECV has been histologically validated for quantification of diffuse myocardial fibrosis [17][18][19] and has been shown to correspond to the histologically measured extent of fibrosis in surgical samples in HCM. 15,20 Contrast-free quantitative cardiac MR techniques have been demonstrated to be promising for evaluating replacement myocardial fibrosis in chronic myocardial infarction.…”
mentioning
confidence: 99%